Systematic and idiosyncratic risks of the U.S. Airline industry - Rafiqul Bhuyan; André Varella Mollick; Md. Ruhul Amin (Journal of Risk and Financial Management, 2022)
Understanding the risky nature of the airline industry has received attention in the tourism literature from separate angles. Although the systematic risk of the airline industry has been examined before, idiosyncratic risk has largely been ignored. This study fills this gap in the tourism literature by investigating the effect of passengers' air travel on systematic and idiosyncratic risks of the U.S. airline industry. Using historical air travel data and utilizing both OLS and fixed-effect models, this paper documents negative relationships between the occupancy of airline seats and idiosyncratic risks for 21 U.S. airline companies. This negative effect of occupancy is more pronounced if air travel distances are shorter, companies have lower leverage ratios, and companies are smaller in size. Policy implications for both airline managers and investors are provided.
Keywords: G12; G32; 650; idiosyncratic risk; airline industry; beta; occupancy of seats; systematic risk